2021
DOI: 10.3233/jifs-201700
|View full text |Cite
|
Sign up to set email alerts
|

q-Rung orthopair fuzzy graphs under Hamacher operators

Abstract: A q-rung orthopair fuzzy set (q-ROFS) is more practical and powerful than intuitionistic fuzzy set (IFS) and Pythagorean fuzzy set (PFS) to model uncertainty in various decision-making problems. In this research article, we introduce the notion of q-rung orthopair fuzzy Hamacher graphs (q-ROFHGs). We utilize the Hamacher operators because they are flexible and parameterized in decision making. We determine the energy of q-ROFHGs as well as the energy of splitting and shadow q-ROFHGs. In addition, we propose th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…As the structure of Hamacher aggregation operators is powerful and massive suitable tool to cope with awkward and complicated information in realistic issues, so keeping in view the importance of Hamacher aggregation operators in the field of fuzzy logic and in the field of decision sciences many scholars have employed the theory of Hamacher aggregation operators in the environment of different fields [40][41][42][43]. In this manuscript the notion of Hamacher aggregation is applied in the environment of linear Diophantine uncertain linguistic sets and is applied in decision making problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the structure of Hamacher aggregation operators is powerful and massive suitable tool to cope with awkward and complicated information in realistic issues, so keeping in view the importance of Hamacher aggregation operators in the field of fuzzy logic and in the field of decision sciences many scholars have employed the theory of Hamacher aggregation operators in the environment of different fields [40][41][42][43]. In this manuscript the notion of Hamacher aggregation is applied in the environment of linear Diophantine uncertain linguistic sets and is applied in decision making problems.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, the principle of Hamacher aggregation operators for complex IFS [40], q-rung orthopair fuzzy graph [41], complex picture fuzzy sets [42], and m-polar fuzzy sets [43] to extend for the presented works.…”
Section: Aggregation Operators Based On Intuitionisticmentioning
confidence: 99%
“…For qROPFSs, a novel method of ranking based on graph theory was given by Khan, Ali and Kumam (2021). Akram, Alsulami, et al (2021) suggested the qROPF Hamacher graphs along with their energy. A qROPFcoefficient of correlation giving only the level of correlation was proposed by Du, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…After that, bipolar fuzzy Hamacher arithmetic and geometric operators were also developed by Wei et al [23]. Akram et al [24] developed q-rung orthopair fuzzy graphs under Hamacher operators.…”
Section: Introductionmentioning
confidence: 99%